PERBANDINGAN PSYCHOLOGICAL WELL-BEING PADA MAHASISWA PSIKOLOGI DAN PENDIDIKAN KHUSUS UNIVERSITAS MUHAMMADIYAH MAHAKARYA ACEH - Khairunnisa, Dinda; Nadia Putri, Riva; Ulandary, Yury (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2023)
Psychological well-being indicates a healthy mental condition marked by happiness, being able to face challenges or problems and use their potential optimally. This study aims to determine differences in the level of psychological well-being between psychology students and special education students at Muhammadiyah Mahakarya University in Aceh. The subjects in this study were 30 individuals consisting of 15 psychology students and 15 special education students. The statistical analysis used was the Independent Sample T-Test. The result of the data analysis test is that there is a significance value of p = 0.000 (p <0.05). The results of this study indicate that there are differences in psychological well-being between psychology students and special education students at Muhammadiyah Mahakarya University in Aceh.